Evaluation of new types sequestering agents and their effect on the model washing of textile materials - Bayerová, Petra; Burgert, Ladislav; Černý, Michal; Krištofíková, Lucia; Hrdina, Radim; Macháček, Vladimír (University of Pardubice, 2015)
A sequestering agent or a chelating agent are the substances capable of removing a metal ion from a solution system via formation of a complex ion that does not possess the reaction activity of the ion removed. These agents are being used to eliminate the water hardness and some metals, such as iron; both having found a wide applicability in the textile industry. The sequestration capacity was measured at 20 °C and 90 °C using media with different pH and in combination with precipitating opacity titration — the so-called Hampshire test. The samples were tested at model washing conditions after 20× repeated washing in hard water (22 °dH, for 30 min at 90 °C) to determine the content of the ash and Ca2+ ions. The image of fabric after such a model washing has then been evaluated with the aid of imaging with a scanning electron microscope.